Performability Estimation of Token Ring Network - Al-Aloosy, Abdul-Kareem A.; Hallaji, Rasha Albert Elia (Nahrain University College of Engineering Journal, 2008)
The work reported in this paper presents a new method for the performability evaluation of the token ring network. Performability is a term used to describeperformance and reliability. Performance is defined as quality of service provided the system is correct . Reliability is the property of a system which allows reliance to be justifiably placed on the service it delivers . However, the problem that arises from evaluating these items separately is that performance depends on reliability. Thus, it is obvious that combining performance and reliability was needed for a complete evaluation; the issue was how to combine them.The method used for performability evaluation of token ring network is based on analysis describing the action of the token ring network. It was assumed that the Mean Time Frame Transfer (MTFT) to be the main measure of the performability which is composed of the Mean Waiting Time (MWT) for a free token and the Mean Real Transfer Time (MRTT) of a data frame (together with the acknowledgement receipt), taking in consideration all possible malfunctions.In addition, the influence of the effective parameters [number of nodes (N), length of the link (L), channel bandwidth (b), exponential distribution ratio of the user access probability ( ) and ratio of malfunctions (km)] on MTFT and its components were investigated. As a general conclusion the present investigation provides a new method for evaluation of performability of the token ring network. It was found that the Mean Time Frame Transfer and its two main omponentsvary linearly with number of nodes, length of the link, exponential distribution ratio of the user access probability and the ratio of malfunction and vary inversely with channel bandwidth.